Industrial, Trade, and Employment Policies in Iran Towards a New Agenda (Springer International Publishing, 2018)
This volume explores Iran's industrial and trade policy options for achieving sustainable, export-oriented, and pro-employment growth. The first part of the book discusses Iran's economic and industrial development performance, as well as strategies for enhancing capabilities, fostering productive transformation, and developing employment that can result in faster and more inclusive economic growth. It also presents a case study on a leading manufacturing subsector-the automotive industry. The book then offers a set of analyses concerning the country's trade sector, including exchange rate policies, ways to connect to global markets, and accession to the World Trade Organization. In turn, the closing chapters investigate various aspects of Iran's labor market and offer policy recommendations on the creation of productive jobs. Readers will learn about effective industrial, trade, and employment policies that can complement macroeconomic measures adopted by the government. As such, the book will appeal not only to scholars and policy-makers, but also to international investors seeking to understand various core aspects of Iran's industrial and employment structures and trade regime. .